The effect of carboxylic acids on the size and shape of Co3O4 nanoparticles: used as capping molecules and ligands in the preparation method - Thabede, P. M. (Vaal University of Technology, 2017)
This study reports the synthesis and characterization of cobalt oxide nanoparticles using a microwave technique and chemical precipitation with oxidation method. Cobalt complexes were prepared using carboxylic acids (acetic acid, heptanoic acid, and stearic acid) as ligands. The complexes were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and Elemental analyses (EA). Cobalt oxide nanoparticles were synthesized from the complexes via a microwave-assisted technique. A precipitation oxidation preparation reaction was used varying different parameters like pH, time, oxidising agent, heating method and cobalt precursor. The use of the cobalt nitrate and cobalt acetate as cobalt precursors resulted in spherical and cubic nanoparticles respectively. Cobalt precursors containing a longer hydrocarbon chain length, for instance cobalt heptanoate, did not yield cobalt oxide nanoparticles with the precipitation oxidation reaction due non- solubility of the complex. Using cobalt acetate as precursor, an increase in the pH from 7.91 to 10.18 caused the cobalt oxide nanoparticles shape to become well defined cubes with a narrower size range and CoOOH needles formed when the pH was further increased to 12.26. The optimum pH of 10.18 yielded cubic cobalt oxide particles having an average size of 25.45 nm with a standard deviation of 6.12. The nanoparticle size decreased from 35.70 nm to 4.45 nm when the oxygen oxidant was replaced with hydrogen peroxide. Conventional heating with a hotplate yielded nanoparticles with a more homogenous shape and size than microwave heating. The size of the nanoparticles increased from 22.81 nm to 25.45 nm when reaction time changed from 16 hours to72 hours.
M.Tech. (Department of Chemistry, Faculty of Applied and Computer Sciences), Vaal University of Technology.
Keywords: Cobalt oxide nanoparticles; Oxidation method; Fourier Transform Infrared Spectroscopy (FTIR); Thermogravimetric Analysis (TGA); Elemental analyses (EA); Nanoparticles; Capping molecules; Ligands; Dissertations, Academic -- South Africa.; Nanoparticles.; Nanostructured materials.